Does pressure to gain social media attention have consequences for adolescents' friendship closeness and mental health? A longitudinal examination of within-person cross-lagged relations. (March 2023) - Dumas, Tara M.; Tremblay, Paul F.; Ellis, Wendy; Millett, Grace; Maxwell-Smith, Matthew A.
Abstract: Many adolescents face pressure when it comes to securing social media attention in the form of views, comments and/or likes on their posted content. The purpose of this study was to examine how this pressure impacts adolescents' current relationships with friends in addition to their mental health over time. Participants were Canadian adolescents (Time 1 n  = 345; M age  = 17.29; 80.6% female) who reported on their felt pressure to gain social media attention, friendship closeness and internalizing symptoms in 3 surveys approximately 4 months apart (from August 2020 to June 2021). We used latent curve modeling with structured residuals (LCM-SR) to model the lagged relations between the aforementioned variables, while also controlling for time spent on social media and number of likes received. LCM-SR builds on multivariate latent curve modeling and autoregressive latent trajectory and allows for the simultaneous testing of between- and within-person stability and change over time. In line with our first hypothesis, results demonstrated that at time points when adolescents experienced more pressure to gain social media attention than usual, their friendship closeness decreased at the next time point. Social media pressure was not a significant predictor of internalizing symptoms, however. Results emphasize the importance of teasing apart within- and between-person effects when examining impacts of adolescent social media use. They also highlight the importance of targeting felt pressures to gain social media attention in order to support healthy adolescent relationships. Highlights: Across 3 time points, between 43.6% and 54.2% of adolescents felt pressure to gain social media attention. Increased social media pressure predicted within-person decreases in friendship closeness at the next time point. Increased social media pressure did not predict changes in internalizing symptoms. To support healthy adolescent relationships, it is important to target felt pressure to gain social media attention.